2022
DOI: 10.3389/fonc.2022.1045481
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade for locally advanced or recurrent/metastatic cervical cancer: An update on clinical data

Abstract: Immunotherapy has shown great promise in the field of oncology, and recent clinical trials have illustrated that immune checkpoint blockade (ICB) is safe and effective at treating a range of tumor types. Cervical cancer (CC) is the fourth most common malignancy in women. However, first-line treatments for locally advanced cervical cancer (LACC) and recurrent/metastatic (R/M) CC have limited efficacy. Thus, it is necessary to explore new treatment approaches. The National Comprehensive Cancer Network (NCCN) cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 122 publications
(132 reference statements)
0
1
0
1
Order By: Relevance
“…Essa glicoproteína de membrana está superexpressa em células de câncer cervical e está associada ao mau prognóstico da doença 35 . Embora o tisotumabe seja uma terapia de primeira linha, outros fármacos mAb podem ser utilizados, como o pembrolizumabe 36 .…”
Section: Discussionunclassified
“…Essa glicoproteína de membrana está superexpressa em células de câncer cervical e está associada ao mau prognóstico da doença 35 . Embora o tisotumabe seja uma terapia de primeira linha, outros fármacos mAb podem ser utilizados, como o pembrolizumabe 36 .…”
Section: Discussionunclassified
“…Finally, studies have shown an increase in the total mutational burden (TMB) rate in CC (approximately 5-6 mutations per megabase) ( 23 , 24 ). Thus, immune checkpoints inhibitors (ICIs) including inhibitors of PD-1 and PD-L1, as well as inhibitors of CTLA-4 have been evaluated in several CC trials ( 5 , 25 ).…”
Section: Systemic Treatment For Recurrent or Metastatic Cervical Cancermentioning
confidence: 99%